"Ethnic polarization and the limits of democratic practice". Issue 8 (17th November 2018) - Shoup, Brian D.
ABSTRACT: While several scholars have speculated that ethnic bipolarity, as a particular type of diversity, is related to the weakness of democracy in multiethnic states there exist few studies that test this relationship. This article suggests that ethnic bipolarity, measured as the size difference of the largest politically relevant ethnic communities and as ethno-political polarization, is related to whether a state exhibits tendencies to limit democratic participation. In cases where the size difference between groups is small or polarization is high there exist incentives to limit full democratic contestation. In the face of international and domestic pressures to politically liberalize, numerically dominant yet demographically insecure groups will seek to democratize only enough to satisfy the minimum needs of transparency while preserving their incumbent position. Using a panel of 121 countries between 1991 and 2014, the results of this analysis suggest that ethnic bipolarity and polarization are a strong predictor of whether a state institutionalizes procedures associated with competitive authoritarian regimes.